PENGARUH KNOWLEDGE MANAGEMENT, KOMPETENSI, DAN KINERJA KARYAWAN FRONT OFFICE TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada Nasabah Bank Rakyat Indonesia di DKI Jakarta) - Rheinyta Ayu Handini (2022)
This research is a type of quantitative research that aims to determine the effect of knowledge management, competence, and employee performance on customer satisfaction. This study uses a sample of customers as respondents from a company engaged in the banking sector, Bank Rakyat Indonesia. The sample used is 100 respondents, with the sample collection technique using accidental sampling. This research hypothesis, namely to determine the effect partially or simultaneously of the independent and dependent variables, so the tests carried out are the coefficient of determination test, t-test, and f-test. From the test results, obtained: (1) Knowledge Management has a positive and significant effect on Customer Satisfaction, (2) Employee Competence has a positive and significant effect on Customer Satisfaction, (3) Employee Performance has a positive and significant effect on Customer Satisfaction, (4) ) Knowledge Management, Employee Competence, and Employee Performance simultaneously has a positive and significant effect on the Customer Satisfaction.